Danhong Injection Enhances the Therapeutic Efficacy of Mesenchymal Stem Cells in Myocardial Infarction by Promoting Angiogenesis - Chen, Jingrui; Wei, Jing; Huang, Yuting; Ma, Yuling; Ni, Jingyu; Li, Min; Zhu, Yan; Gao, Xiumei; Fan, Guanwei (Frontiers in Physiology, 2018)
Stem cell–based therapies have the potential to dramatically transform the treatment and prognosis of myocardial infarction (MI), and mesenchymal stem cells (MSCs) have been suggested as a promising cell population to ameliorate the heart remodeling in post MI. However, poor implantation and survival in ischemic myocardium restricts its efficacy and application. In this study, we sought to use the unique mode of action of Chinese medicine to improve this situation. Surrounding the myocardial infarct area, we performed a multi-point MSC transplantation and administered in conjunction with Danhong injection (DHI), which is mainly used for the treatment of MI. Our results showed that the MSC survival rate and cardiac function were improved significantly through the small animal imaging system and echocardiography, respectively. Moreover, histological analysis showed that MSC combined with DHI intervention significantly reduced myocardial infarct size in myocardial infarcted mice and significantly increased MSC resident. To investigate the mechanism of DHI promoting MSC survival and cell migration, PCR and WB experiments were performed. Our results showed that DHI could promote the expression of CXC chemokine receptor 4 (CXCR4) in MSC and enhance the expression of stromal cell - derived factor-1 (SDF-1) in myocardium, and this effect can be inhibited by AMD3100 (an SDF1/CXCR4 antagonist). Additionally, MSC in combination with DHI interfered with MI in mice and this signifies that when combined, the duo could the expression of vascular endothelial growth factor (VEGF) in the marginal zone of infarction compared with when either MSC or DHI are used individually. Based on these results, we conclude that DHI enhances the residence of MSCs in cardiac tissue by modulating the SDF1/CXCR4 signaling pathway. These findings have important therapeutic implications for Chinese medicine-assisted cell-based therapy strategies.